Root traits and arbuscular mycorrhiza on perennial grasses exposed to defoliation after a controlled burning - Ithurrart, Leticia S. (2018)
Plant competition for soil resources is common in semiarid rangelands. Plants have various, alternative mechanisms to deal with soil resource acquisition. They include (1) length, weight and proliferation of roots, (2) root length density, and (3) root colonization by arbuscular mycorrhiza. In rangelands of Argentina, plants are exposed to herbivory after natural fires. As a result, knowledge on how these disturbances impact root traits is important for outlining guidelines focused on rangeland management and improvement. Our aim was to analyze the effects of defoliation after a controlled burning on root traits (1) to (3) on two preferred (Poa ligularis and Nassella tenuis) and one unpreferred (Amelichloa ambigua) perennial grasses. Applied treatments did not affect neither root length nor percentage colonization by arbucular mycorrhiza. The smaller diameter and greater root length found in P. ligularis might contribute to explain its lower root mycorrhizal colonization in comparison to A. ambigua and N. tenuis, respectively. The greatest root length and weight, on P. ligularis will contribute to explain the already known greater competitive ability in this than in the other two study species. Our results suggest that defoliating P. ligularis after fire would not compromise its competitive ability, thus contributing to rangeland management.